Ceftriaxone-Induced Immune Hemolytic Anemia: In Vitro Reversal with Peptide Inhibitor of Complement C1 (PIC1) - Kenji M. Cunnion; Lisa M. Feagin; Michael F. Chicella; Cortney L. Kaszowski; Pamela S. Hair; Jessica Price; William C. Owen (Case Reports in Hematology)
We report a case of ceftriaxone-induced immune hemolytic anemia in a 10-year-old with chronic active Epstein–Barr virus disease and hemophagocytic lymphohistiocytosis. After chemotherapy, she became febrile and received ceftriaxone. She rapidly developed respiratory failure and anemia. Her direct antiglobulin test was positive for IgG and C3. To confirm this was ceftriaxone-induced complement-mediated hemolysis, we adapted the complement hemolysis using human erythrocytes (CHUHE) assay by adding exogenous ceftriaxone to the patient’s serum which enhanced lysis of her erythrocytes. We confirmed that ceftriaxone initiated a classical complement pathway-mediated hemolysis by in vitro reversal with peptide inhibitor of complement C1 (PIC1).